O-012 Onyx embolization of intracranial arteriovenous malformations in pediatric patients. (12th July 2011) - Soltanolkotabi, M; Ansari, S; Hurley, M; Alden, T; Bendok, B; Shaibani, A
Abstract : Objective: The use of ethylene-vinyl alcohol copolymer (Onyx) in the treatment of intracranial arteriovenous malformations (AVMs) has increased the cure rate of endovascular embolization compared with the use of liquid adhesive agents. The initial success of this polymer in the adult population has resulted in its increased utilization in children. Yet, its efficacy and safety in the pediatric population have not been firmly established. We report our experiences in the treatment of intracranial AVMs in 21 pediatric patients. To our knowledge, this is the largest series of Onyx embolization of pediatric intracranial AVMs reported in the literature. Methods: Between August 2005 and December 2010, 21 patients with intracranial AVMs were embolized with Onyx. We studied patient age, demographics, clinical presentations, AVM characteristics, embolization procedures, complications, clinical (modified Rankin Scale) and technical (calculated volume reduction) outcomes, and post-surgical assessment (total/partial resection and complications). Results: The patients' ages ranged from 6.91 to 17.08 years (mean =11.25) and 14 were males and 7 females. Clinical presentation included hemorrhage (47.6%), headache (28.6%), seizure (9.5%), and in three patients the AVM was an incidental finding (14.3%). A baseline modified Rankin Scale Score was calculated for each patient upon presentation. Mean calculated size of the AVM was 6.2 ml (range=0.4–13.5 ml). 32 embolization sessions were performed, ranging from one to four per patient. Average estimated size reduction was 72% (median=80%, range 0–100%). Complete obliteration was achieved in two AVMs (9.5%). Partial embolization was performed for surgical resection in 19 patients with one patient requiring subsequent radiosurgery. Complications following embolization occurred in six patients, leading to permanent disability in one patient (morbidity 4.8%), but no patients deaths (mortality 0%). Device-related complications occurred during 2 of the embolization procedures (6.25%), with no clinical consequences. The injection of Onyx resulted in high occlusion rates (mean volume reduction=82.7%) when the AVM was supratentorial and cortically located, the nidus was compact and plexiform, and when there was a small number of supplying feeders and superficial draining veins. Total resection of the AVM was achieved post-operatively in 18 patients whereas one AVM was only partially resected. Symptomatic complications following surgical resection occurred in seven patients (33.3%) with 6 cases of focal neurologic deficits and one case of seizure related to post-operative hemorrhage. Patients were followed for an average period of 144 days post-operatively (range =12 days to 40 months). Modified Rankin Scale Scores were calculated after treatment and compared with baseline scores with the majority demonstrating stability or improvement in functional outcome following treatment (17 patients). Conclusion: Onyx embolization can be performed with a high degree of technical success allowing safe and complete resection of intracranial AVMs with a low rate of neurological complications in the pediatric population. Complete obliteration can be achieved in small AVMs. Large AVMs can be adequately reduced in size for additional surgical or radiosurgical treatment. Long-term follow-up data will be necessary to assess the continued efficacy and safety of this agent in children.